An exploratory analysis of global trends in wheelchair service provision knowledge across different demographic variables: 2017–2020. Issue 2 (4th March 2023) - Goldberg, Mary; Alharbi, Mohammed; Kandavel, Krithika; Burrola-Mendez, Yohali; Augustine, Nancy; Toro-Hernández, Maria L.; Pearlman, Jonathan
ABSTRACT: To explore global trends in manual wheelchair service provision knowledge across geographic, professional, and socioeconomic domains. A secondary analysis of a dataset from the International Society of Wheelchair Professionals' Wheelchair Service Provision Basic Knowledge Test was conducted. The dataset included test takers from around the world and was extracted from Test.com and International Society of Wheelchair Professionals' Wheelchair International Network. Participants 2, 467 unique test takers from 86 countries. Interventions Not applicable. International Society of Wheelchair Professionals' Wheelchair Service Provision Basic Knowledge Test. We identified significant inverse associations between pass rate and the following variables: education (high school and some college), test taker motivation (required by academic program or employer), and country income setting (low and middle). There were significant positive associations between pass rate and the following variables: training received (offered by Mobility India or 'other NGO'), and age group served (early childhood). Global wheelchair knowledge trends related to key variables such as training, occupation, and income setting have been preliminarily explored. Future work includes further validation of the primary outcome measure and recruitment of a larger sample size to further explore significant associations between additional test taker variables.